Association between maternal khat use and other determinants and low birth weight in Halaba Zone, South Ethiopia: an unmatched case–control study - Wogayehu, Biruk; Demissie, Tsegaye; Wolka, Eskinder; Alemayehu, Mekuriaw (Frontiers in Pediatrics, 2025)
IntroductionEarly newborn mortality, morbidity, and long-term health outcomes are significantly predicted by birth weight. Many babies are born underweight in Ethiopia, but few case–control studies have previously examined the risk variables associated with khat consumption and low birth weight (LBW). Therefore, the aim of this study was to identify maternal khat use and maternal sociodemographic and obstetric risk factors associated with LBW in the Halaba Kulito General Hospital, southern Ethiopia.MethodsA hospital-based case–control study design was used on 334 neonates (111 cases and 223 controls) at Halaba General Hospital in Halaba Zone, southern Ethiopia, from 01 October 2023 to 27 February 2024. A consecutive sampling method was used to select both the cases and controls. Bi-variable and multivariable logistic regression models were fitted using Stata 14.0 to estimate the effect of maternal khat use and other factors on low birth weight. A p-value of <0.05 was considered a significant difference in low birth weight between the cases and controls.ResultsWe found that the mean age of the cases and controls at birth was 25.4 ± 4.57 years and 24.2 ± 3.96 weeks, respectively. Illiteracy [adjusted OR (AOR) = 3.7, 95%CI 1.34, 10.45], rural residence (AOR = 4.1, 95%CI 1.51, 11.35), gestational age <37weeks (AOR = 16.5, 95%CI 7.05, 38.55), maternal mid-upper arm circumference (MUAC) <23 cm (AOR = 4.7, 95%CI 1.89, 11.65), weight gain <12 kg (AOR = 4.8, 95%CI 1.22, 18.59), monthly khat use (AOR = 9.5, 95%CI 2.13, 41.98), weekly khat use (AOR = 11.1, 95%CI 3.69, 33.40), and daily khat use (AOR = 14.1, 95%CI 4.74, 42.03) were the determinant factors for delivering a newborn with low birth weight.ConclusionThe evidence from this study suggests that illiteracy, rural residence, gestational age <37weeks, maternal MUAC <23 cm, weight gain <12 kg, monthly khat use, weekly khat use, and daily khat use were independent predictors of low birth weight. Suggested strategies involve the early identification and management of identified modifiable variables. We recommend that stakeholders in khat control commit to providing health education and awareness, incorporating khat use among women in the khat control policy, and designing interventions for the cessation of khat use among women.